Regulation of Arabidopsis defense responses against Spodoptera littoralis by CPK-mediated calcium signaling - Kanchiswamy, Chidananda Nagamangala (BioMed Central, 2010)
BACKGROUND: Plant Ca(2+ )signals are involved in a wide array of intracellular signaling pathways after pest invasion. Ca(2+)-binding sensory proteins such as Ca(2+)-dependent protein kinases (CPKs) have been predicted to mediate the signaling following Ca(2+ )influx after insect herbivory. However, until now this prediction was not testable. RESULTS: To investigate the roles CPKs play in a herbivore response-signaling pathway, we screened the characteristics of Arabidopsis CPK mutants damaged by a feeding generalist herbivore, Spodoptera littoralis. Following insect attack, the cpk3 and cpk13 mutants showed lower transcript levels of plant defensin gene PDF1.2 compared to wild-type plants. The CPK cascade was not directly linked to the herbivory-induced signaling pathways that were mediated by defense-related phytohormones such as jasmonic acid and ethylene. CPK3 was also suggested to be involved in a negative feedback regulation of the cytosolic Ca(2+ )levels after herbivory and wounding damage. In vitro kinase assays of CPK3 protein with a suite of substrates demonstrated that the protein phosphorylates transcription factors (including ERF1, HsfB2a and CZF1/ZFAR1) in the presence of Ca(2+). CPK13 strongly phosphorylated only HsfB2a, irrespective of the presence of Ca(2+). Furthermore, in vivo agroinfiltration assays showed that CPK3-or CPK13-derived phosphorylation of a heat shock factor (HsfB2a) promotes PDF1.2 transcriptional activation in the defense response. CONCLUSIONS: These results reveal the involvement of two Arabidopsis CPKs (CPK3 and CPK13) in the herbivory-induced signaling network via HsfB2a-mediated regulation of the defense-related transcriptional machinery. This cascade is not involved in the phytohormone-related signaling pathways, but rather directly impacts transcription factors for defense responses.